Towards an Understanding of Value Creation in Agile Software Development - G. Neto, Geraldo Torres; Santos, Wylliams B.; Fagundes, Roberta A. A.; Margaria, Tiziana (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Recently, studies involving the creation of business value in Agile Software Development (ASD) have been growing substantially. However, the concept of value creation in ASD has not yet been clearly defined. Besides, the literature does not define practices that can create business value for ASD. Identifying these practices can change the mindset of agile teams, since surveys indicate that, from the point of view of the agile team, the creation of value is poorly understood. Thus, this study carried out a Systematic Literature Review to identify how value creation is defined in ASD, and how practices can improve this value creation. Despite the lack of studies on the subject, we identified practices and its positive and negative influence on value creation.